Web-Based Online Exhibition by Implementing Virtual and Augmented Reality to Visualize Architecture Building Design - Ketut Nova Wirya Dinata Dinata; I Gede Partha Sindu Sindu; Dessy Seri Wahyuni Wahyuni (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2023)
Web-based online exhibition using immersive technology, namely Virtual Reality & Augmented Reality, has a major effect on the efficiency of time, place, and cost in providing visitors with an understanding of building architecture. Interaction in understanding architectural modeling is also assisted by a technology called Avatar Mediated Communication (AMC) which is the scope of interaction with other visitors in a Virtual Environment created by Virtual Reality technology. Technology that is able to support all website-based reality activities is made with the Laravel & Express Js framework (Website), Spoke Mozilla Hubs (Virtual Reality Environment), and Library AR Js (Augmented Reality Marker Based). The technology is selected, built, and combined in the stages of the Research & Development (R&D) method, the Multimedia Development Life Cycle (MDLC) model in examining the development stages and user responses to web-based Virtual & Augmented Reality development products. The results of the responses obtained are based on 6 categories in the UEQ (User Experience Questionnaire) instrument. The result showed that the three largest categories that give a positive response are stimulation, attractiveness, and novelty. Meanwhile, the three categories below are efficiency, perspicuity, and dependability. This indicates that the online exhibition in the support of immersive visualization is able to increase user curiosity in trying to enter the virtual reality room presented in web-based Virtual & Augmented Reality.